ANTHROPOMETRIC CHARACTERISTICS OF SCHOOLS IN THE MUNICIPAL PUBLIC OF ARAPIRACA, ALAGOAS ABSTRACT (Fiep Bulletin - online, 2012)
The study aimed to evaluate the anthropometric characteristics of schoolchildren of both sexes enrolled in a public school in the city of Arapiraca-AL in 2010. The sample consisted of 620 schoolchildren of both sexes, aged 9 years, enrolled in a school in the municipal Arapiraca, Alagoas. We measured total body mass and height (to calculate body mass index - BMI), waist circumference as well as anatomical and skin folds. To collect data to utlize a balance Techline BAL-150Pa®, a Sanny stadiometer®, a metal anthropometric tape Sanny® and a skinfold caliper Sanny®. We used the statistic of central tendency. For both sexes the results indicate that schoolchildren are within the normal range for height by age for BMI, waist to anatomical and relative body fat. It is concluded that for both sexes, mean values ??were within normal range, however, females had higher levels of relative body fat.
Keywords: Anthropometry; school; Obesity.